Karakteristik Kimia dan Sensori Egg Roll Berbahan Dasar Tepung Ubi Jalar Ungu dengan Substitusi Tepung Umbi Porang - Novidahlia, Noli; Nurlaela, Raden Siti; Saniyya, Ashila Nasyadhiya (JURNAL AGROINDUSTRI HALAL, 2025)
Egg roll consumption in 2022 reached 22,185%/capita/year. The purpose of the study was to study the effect of the comparison of purple sweet potato flour with porang tuber flour on chemical analysis, sensory quality, and hedonic. This study used a 1-factor Complete Randomized Design, namely the comparison of the concentration of purple sweet potato flour with porang tuber flour. It has 4 treatment levels, consisting of 100%: 0%, 90%: 10%, 80%: 20%, 70%: 30%, and 2 replications. The parameters tested include chemical analysis, sensory quality, and hedonic. The results showed that the addition of porang tuber flour can increase ash content, protein, carbohydrates, texture sensory, and the level of acceptance in terms of taste, aroma, and texture, but reduce fat content and color acceptance level. The selected egg roll product in this study, namely the comparison of the concentration of purple sweet potato flour 70% with porang tuber flour 30%. Having a water content of 3.31%, ash 3.04%, protein 2.94%, fat 22.83%, carbohydrate 67.88%, crude fiber 33.51%. The results of the sensory quality test of purple color, sweet taste, and crunchy texture tend to be strong. The results of the hedonic test of all parameters tend to like.